Mechanism of periodic height variations along self-aligned VLS-grown planar nanostructures - Steele, J.A.; Horvat, J.; Lewis, R.A.; Henini, M.; Fan, D.; Mazur, Yu.I.; Dorogan, V.G.; Grant, P.C.; Yu, S.Q.; Salamo, G.J. (Royal Society of Chemistry, 2015)
In this study we report in-plane nanotracks produced by molecular-beam-epitaxy (MBE) exhibiting lateral self-assembly and unusual periodic and out-of-phase height variations across their growth axes. The nanotracks are synthesized using bismuth segregation on the GaAsBi epitaxial surface, which results in metallic liquid droplets capable of catalyzing GaAsBi nanotrack growth via the vapor–liquid–solid (VLS) mechanism. A detailed examination of the nanotrack morphologies is carried out employing a combination of scanning electron and atomic force microscopy and, based on the findings, a geometric model of nanotrack growth during MBE is developed. Our results indicate diffusion and shadowing effects play significant roles in defining the interesting nanotrack shape. The unique periodicity of our lateral nanotracks originates from a rotating nucleation “hot spot” at the edge of the liquid–solid interface, a feature caused by the relative periodic circling of the non-normal ion beam flux incident on the sample surface, inside the MBE chamber. We point out that such a concept is divergent from current models of crawling mode growth kinetics and conclude that these effects may be utilized in the design and assembly of planar nanostructures with controlled non-monotonous structure.